Intra-generational Social Mobility and Entrepreneurship in Uruguay - Daniel Bukstein; Nestor Gandelman (Inter-American Development Bank (IDB), 2012)
This paper follows an income-based, time-dependence approach to measure social mobility in Uruguay between 1982 and 2010. The paper finds that social mobility in Uruguay is considerable and reports evidence suggesting that this mobility is greater within cohorts of groups, such as those defined by gender or region, than between groups. Entrepreneurship and self-employment are associated with greater social mobility.
Keywords: D31; L26; O15; 330